2018
DOI: 10.1177/1352458518813108
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of functional brain network reorganization in clinically isolated syndrome

Abstract: Background: There is a lack of longitudinal studies exploring the topological organization of functional brain networks at the early stages of multiple sclerosis (MS). Objective: This study aims to assess potential brain functional reorganization at rest in patients with CIS (PwCIS) after 1 year of evolution and to characterize the dynamics of functional brain networks at the early stage of the disease. Methods: We prospectively included 41 PwCIS and 19 matched healthy controls (HCs). They were scanned at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
(59 reference statements)
2
19
1
Order By: Relevance
“…At baseline, increased connectivity in the right middle temporal gyrus was observed in CIS; moreover, after a one year follow-up, both a higher degree in the hippocampi, cingulate cortex and in the left parieto-occipital sulcus, and a reduced degree in the middle occipital gyrus and left posterior segment of the lateral fissure were observed. Hub reorganization correlated with better cognitive scores; conversely, no significant correlations were reported with clinical scores and white matter lesions [93].…”
Section: Brain Network Reorganization In Msmentioning
confidence: 73%
See 2 more Smart Citations
“…At baseline, increased connectivity in the right middle temporal gyrus was observed in CIS; moreover, after a one year follow-up, both a higher degree in the hippocampi, cingulate cortex and in the left parieto-occipital sulcus, and a reduced degree in the middle occipital gyrus and left posterior segment of the lateral fissure were observed. Hub reorganization correlated with better cognitive scores; conversely, no significant correlations were reported with clinical scores and white matter lesions [93].…”
Section: Brain Network Reorganization In Msmentioning
confidence: 73%
“…Notably, in CIS patients rich club connectivity was preserved and alterations mostly involved feeders connecting rich club to non-rich club nodes and local connections [92]. One rs-fMRI study explored brain network reorganization in a group of CIS patients at baseline and after a one year follow-up [93] by calculating the hub disruption index, a useful and reliable measure of large-scale networks reorganization [94,95]. With such an approach, a significant hub reorganization was detected at baseline and even more after one year, showing the occurrence of brain regions with reduced and increased connectivity at the same time [93].…”
Section: Brain Network Reorganization In Msmentioning
confidence: 99%
See 1 more Smart Citation
“…To objectify reorganization of the functional networks, we defined a hub disruption index κ, which has already been used in studies in comatose patients, patients with stroke, lateralized focal epilepsies and clinically isolated syndrome (CIS) but never in patients with NMOSD [14,1921]. These studies demonstrated a reorganization of brain networks with both disconnected and overconnected nodes in patients and a reduced hub disruption index κ in comparison with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…We recently summarized the basic concepts, and limitations, of functional brain reorganization in MS (26). Even from early disease phases-in patients with CIS-dynamic changes in functional brain networks have been observed, resulting in the maintenance of normal efficiency in the brain and consequently representing a compensatory effect (27). A mixed pattern of hypoactivity and hyperactivity was found, by means of rs-fMRI, in pwMS at different stages of disease.…”
Section: Network-connectivity-brain Reorganizationmentioning
confidence: 99%